Analisis Peran Ekonomi Kreatif Dalam Meningkatkan Pendapatan Pengrajin Sampah Plastik Ditinjau Dari Perspektif Etika Bisnis Islam (Studi Di Kasus Pada UMKM Pengolahan Sampah Plastik, Jalan Riau, Kecamatan Medan Belawan) - Fauziah, Fauziah; M. Nawawi, Zuhrinal; Mawaddah, Mawaddah (Universitas Labuhanbatu, 2022)
Creative economy is an economic activity that prioritizes creativity thinking to create something new and different, which has value and is commercial or useful. MSMEs are one of the sectors in the creative economy, because MSMEs are labor-intensive businesses that require creativity or expertise for their workers. This study aims to determine the role of the creative economy in increasing the income of plastic waste craftsmen, viewed from the perspective of Islamic Business Ethics. This research approach is qualitative by using descriptive analysis. The data sources used are primary data and secondary data with data collection techniques in the form of observation, interviews, and documentation. The result of this study is that all craftsmen experienced an increase in income, it shows that the creative economy plays a role in increasing the income of all plastic waste processing craftsmen in Riau Street, Medan Belawan District and evidenced by the results of interviews conducted directly with all craftsmen. In addition, this MSME has also applied the principles of Islamic Business Ethics in its business, this can be seen from the attitude of craftsmen who are responsible in their business, doing worship such as prayer, fasting, alms, being honest, selling good quality goods, being generous, building good relationships between fellow colleagues, orderly administration, setting prices transparently, keeping promises, to responsibilities that certainly have a good effect on increasing the income received by craftsmen.